Regarding a Pre-Distorted ADO-OFDM System as a DCO-OFDM System for Visible Light Communications - Shih-Kai Lee (IEEE, 2021)
We provide an interpretation for a recently proposed pre-distorted asymmetrically clipped DC-biased optical orthogonal frequency division multiplexing (ADO-OFDM) system. Through our derivation, we find that the predistorted ADO-OFDM system can be regarded as a direct current biased optical OFDM (DCO-OFDM) system in which the odd-index and the even-index subcarriers are based on different power assignments. For multipath channels that have no channel side information (CSI), the mechanism for power allocation and adaptive modulation is impractical. Using state-of-the-art polar coding that includes an interleaver is appropriate to combat such a situation. The performance comparison between an interleaved polar coded ADO-OFDM system both with and without pre-distortion are simulated and concluded.